2022
DOI: 10.3390/nu14194107
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Association of Copper and Copper-to-Zinc-Ratio in Hair with Acute Coronary Syndrome Occurrence and Its Risk Factors

Abstract: The prevalence of coronary artery disease (CAD) increases every year; however, the impact of microelements on its underlying cause—atherosclerosis—is still unclear. Copper plays numerous regulatory roles in cardiovascular health and was suggested to influence the classic risk factors for CAD. The copper-to-zinc-ratio (Cu/Zn-ratio) reflects systemic oxidative stress–one of the factors in the complex pathogenesis of atherosclerosis. Hair incorporates metal ions during its growth; thus, it reflects the metal expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Nonetheless, a subset of studies found a positive correlation [18] or, in some instances, a lack of the correlation [19,20]. Similar inconsistent results have been described regarding the correlation between Cu and the Cu to Zn (Cu/Zn) ratio with CVD [18,[21][22][23].…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Nonetheless, a subset of studies found a positive correlation [18] or, in some instances, a lack of the correlation [19,20]. Similar inconsistent results have been described regarding the correlation between Cu and the Cu to Zn (Cu/Zn) ratio with CVD [18,[21][22][23].…”
Section: Introductionmentioning
confidence: 69%
“…Our previous analyses failed to reveal differences in the concentration of Zn and Cu and the Cu/Zn ratio when comparing patients with acute coronary syndrome (ACS) to those diagnosed with CAD [19,21]. These parameters were similar across patients displaying differing degrees of atherosclerosis.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…2D). It is important to note that various factors, such as age, health condition, diet, and intake of other nutrients, may in uence the levels of Zn (Dziedzic et al, 2022). Both a de ciency and an excess of Zn can have detrimental effects on cognitive function (Babic Leko et al, 2021).…”
Section: Correlation Analysis Between Wb and Qrt-pcr Veri Cation Resu...mentioning
confidence: 99%
“…In addition, excess copper triggers Huntington’s disease by promoting the accumulation of Huntingtin proteins as well as inhibiting the activity of mitochondrial dehydrogenases ( Mason et al, 2013 ; Xiao et al, 2013 ). Interestingly, high serum copper levels are associated with an increased risk of atherosclerotic disease, and conversely copper deficiency may contribute to hypertrophic cardiomyopathy ( Dziedzic et al, 2022 ; Farrant et al, 2023 ). However, little is known about the mechanism of copper in carcinogenesis.…”
Section: Mechanism Of Copper In Carcinogenesismentioning
confidence: 99%